AN ANALYSIS OF TYPES OF STUDENTS’ MISBEHAVIOURS IN EFL CLASSROOM - Dian Indah Kusuma; Ahmad Talib; Syarifah Farahdiba (Bahasa Inggris Program Sarjana Terapan, Universitas Negeri Makassar, 2025)
This research conducted at MTS Guppi Pesuloang and 16 seventh grade students and an English teacher were the subject in this research. This research is a qualitative descriptive that aims to find out the types of student misbehavior that appear in the EFL class. Student misbehavior as a single variable. This research has two instruments, namely the observation checklist and interview. From the research it was found that there were 7 misbehaviors committed by students in the process of learning English in the classroom during the research, namely 1) Ignoring the uniform rules, 2) Not paying attention to teacher's explanation, 3) Distrupting classmates, 4) Using google translate, 5) Diverting the conversation from the subject matter, 6) Disobeying teacher's instructions, and 7) Talking too much.